Constructing self-esteem: Authoritative da’wah material in Syi’ir Ngudi Susilo by Bisri Mustofa - Ansori, Mohammad; Ningsih, Yusria; Jaili, Hambali (Jurnal Ilmu Dakwah, 2025)
Purpose – The purpose of this study is to analyze how Syi'ir Ngudi Susilo by Bisri Mustofa constructs and conveys the concept of self-esteem as an authoritative da’wah material Method – This study used a qualitative method with a semiotic analysis approach. The data collection techniques included reading and note-taking. The data analysis methods used the Agih Method and the Match Method. Result – The results showed that the construction of self-esteem in the Syi’ir Ngudi Susilo is achieved by identifying elements related to self-esteem in the Syi’ir. These elements include self-knowledge, self and others, self-acceptance, self-reliance, self-expression, self-confidence, and self-awareness. These elements align with the concept of self-esteem development, which includes the practices of living consciously, self-acceptance, self-responsibility, self-assertiveness, living purposefully, and personal integrity. Ngudi Susilo communicates authoritative da'wah material effectively in an aesthetic, emotional, and easy-to-understand manner. Implication – The study has several significant implications in the fields of Islamic preaching (da’wah), education, psychology, and cultural studies. These implications highlight the broader impact of syi'ir in shaping religious understanding, promoting self-esteem, and preserving traditional Islamic literary forms Originality/Value – This study is the first study that breaks new ground by using Saussure’s semiotic framework to examine how syi'ir constructs self-esteem and serves as an authoritative da'wah material. The syi'ir is not only just a religious or artistic form but also a therapeutic tool for personal and social development. *** Tujuan – Tujuan penelitian ini adalah untuk menganalisis bagaimana Syi'ir Ngudi Susilo karya Bisri Mustofa membangun dan menyampaikan konsep harga diri sebagai bahan dakwah yang otoritatif.  Metode – Penelitian ini menggunakan metode kualitatif dengan pendekatan analisis semiotik. Teknik pengumpulan data meliputi pembacaan dan pencatatan. Metode analisis data yang digunakan adalah Metode Agih dan Metode Match. Hasil – Hasil penelitian menunjukkan bahwa pembentukan harga diri dalam Syi’ir Ngudi Susilo dicapai dengan mengidentifikasi unsur-unsur yang berkaitan dengan harga diri dalam Syi’ir. Unsur-unsur tersebut meliputi pengetahuan diri, hubungan diri dengan orang lain, penerimaan diri, kemandirian, ekspresi diri, kepercayaan diri, dan kesadaran diri. Elemen-elemen ini sejalan dengan konsep pengembangan harga diri, yang mencakup praktik hidup secara sadar, penerimaan diri, tanggung jawab diri, keberanian diri, hidup dengan tujuan, dan integritas pribadi. Ngudi Susilo menyampaikan materi dakwah secara efektif dengan cara yang estetis, emosional, dan mudah dipahami. Implikasi – Studi ini memiliki beberapa implikasi signifikan di bidang dakwah Islam, pendidikan, psikologi, dan studi budaya. Implikasi ini menyoroti dampak yang lebih luas dari syi'ir dalam membentuk pemahaman agama, mempromosikan harga diri, dan melestarikan bentuk sastra Islam tradisional. Orisinalitas/Nilai – Studi ini merupakan studi pertama yang membuka jalan baru dengan menggunakan kerangka semiotik Saussure untuk menganalisis bagaimana syi'ir membangun harga diri dan berfungsi sebagai materi da'wah yang otoritatif. Syi'ir tidak hanya sekadar bentuk keagamaan atau seni, tetapi juga alat terapeutik untuk pengembangan pribadi dan sosial.